Directionally aligned macroporous SiOC via freeze casting of preceramic polymers. Issue 8 (August 2015) - Naviroj, M.; Miller, S.M.; Colombo, P.; Faber, K.T.
Abstract A commercially available polysiloxane was used as a preceramic polymer for solution freeze casting to obtain directionally aligned porous silicon oxycarbide. We show how choice of solvent, polymer concentration, and freezing rate can affect the final pore network of the freeze-cast ceramic. Solvents of cyclohexane and camphene resulted in dendritic pores, while tert-butyl alcohol (TBA) produced intersecting cellular pores in the freeze-cast ceramic. Characterization of pore size distribution by mercury intrusion porosimetry of ceramics produced from cyclohexane–polysiloxane solutions with varying polymer concentrations and freezing rates demonstrated trends consistent with solidification theory. Fourier transform infrared spectroscopy and X-ray diffraction were employed to confirm that the freeze-casting process resulted in silicon oxycarbide of comparable chemistry and crystallinity to that produced via traditional preceramic polymer processing techniques.